2019
DOI: 10.1177/1539449219876877
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to Modify Habits: A Scoping Review

Abstract: Intervening to change clients’ habits in the course of their everyday occupations could improve health. Habit formation interventions are an emerging area of science, however, and there is a need to better understand the current state of habit intervention research. The objective of this study is to examine the evidence related to habit formation interventions to modify health habits among adults. We performed a scoping review of peer-review articles published since January 1, 2008. The majority of the 18 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Furthermore, the findings about the mediating roles of self-regulation in the relationship between intervention and habit strength indicate that the employment of self-regulation would be an effective strategy for habit formation. This finding empirically supports the framework for understanding habit formation and its determinants [ 33 , 40 ] and strengthens the current evidence about the strategies of habit [ 41 ]. However, the desirable effect of forming habit on behavior change was not replicable in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the findings about the mediating roles of self-regulation in the relationship between intervention and habit strength indicate that the employment of self-regulation would be an effective strategy for habit formation. This finding empirically supports the framework for understanding habit formation and its determinants [ 33 , 40 ] and strengthens the current evidence about the strategies of habit [ 41 ]. However, the desirable effect of forming habit on behavior change was not replicable in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…A review of self-regulation also argued that attempting to automate behavior is important for successful self-regulation [ 5 ]. Intervention studies have employed planning to form habits [ 41 ]. However, although self-regulation strategies are widely accepted as a way of forming a habit, few intervention studies have confirmed their mediation process.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding differences in how men and women perceive habit formation treatment may be especially important in designing weight loss interventions. Although the goal of habit formation treatment is to increase the automaticity of behaviors, individuals must make conscious serious efforts to modify their behavior (Fritz et al, 2020). Present results indicate that men may be harder to motivate for making such effort.…”
Section: Discussionmentioning
confidence: 99%
“…Building Toward Sustainability is a cognitive-behavioral construct that addresses the "why" of the behavior change and the emerging core identity as one that enacts these healthy behaviors. Behavior-change literature has shown the sustainability of outcomes in the short term, such as a few weeks or months; however, sustaining results beyond six months is difficult, especially in obesity management [13]. To effect long-term sustainable changes, the NHC uses strategies to support permanent habits that help the target behavior [14,15], such as a "coupling ritual" anchoring medication to eating breakfast at the kitchen table every morning, which then transfers (i.e., cascade effect) to including healthier food choices at breakfast [9,[13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%